A mortality score for acute respiratory distress syndrome: predicting the future without a crystal ball - Santos, Raquel S.; Silva, Pedro L.; Rocco, Jose Rodolfo; Pelosi, Paolo; Macêdo Rocco, Patricia Rieken (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
In a recent paper published in Critical Care Medicine, Villar et al. (1) proposed a scoring system that could be easily calculated at the bedside to predict mortality in patients with acute respiratory distress syndrome (ARDS) 24 hours after diagnosis. As in-hospital mortality ranges from 34.9% to 46.1% across the spectrum of mild to severe ARDS, respectively, the potential for improvement in management of patients with this syndrome remains high (2). Based on 62 recorded variables, age, oxygenation (PaO2/FiO2), and the plateau airway pressure score (APPS) were chosen to establish a 9-point stratification 24 hours after ARDS diagnosis, followed by categorization into low, intermediate, and high risk of death with predictive validity. The APPS classified ARDS into three severity subgroups (7 points), and significantly higher mortality was observed in those patients with an APPS greater than 7 (>80%) compared to those with an APPS of less than 5 (